Fabrication, microstructure and optical characterizations of holmium oxide (Ho2O3) transparent ceramics. Issue 1 (January 2021) - Hu, Dianjun; Li, Xiaoying; Snetkov, Ilya; Yakovlev, Alexey; Balabanov, Stanislav; Ivanov, Maxim; Liu, Xin; Liu, Ziyu; Tian, Feng; Xie, Tengfei; Palashov, Oleg; Li, Jiang
Abstract: Ho2 O3 transparent ceramics were fabricated by vacuum pre-sintering combined with hot isostatic pressing (HIP) post-treatment at relatively low temperature from high-purity Ho2 O3 powder calcined at 1000 °C for 4 h. The optimal Ho2 O3 ceramic sample prepared by vacuum pre-sintering at 1250 °C and HIP post-treating at 1450 °C has a dense microstructure with average grain size of 0.77 μm, and the in-line transmittances reach 80.7 % at 1550 nm and 76.7 % at 1064 nm. The effect of air annealing on the optical quality of Ho2 O3 ceramics was studied, and the existence of compressed pores in the HIP-ed Ho2 O3 ceramics was confirmed. The Verdet constants of Ho2 O3 ceramics were measured to be -47.4 rad/(T m at 1064 nm and -15.4 rad/(T m at 1561 nm. High transmittance and large Verdet constant in the wavelength regions 1–1.07 μm, 1.3–1.5 μm make Ho2 O3 transparent ceramics promising for magneto-optical devices for lasers based on Yb-, Nd-doped materials and telecom lasers.